Metastatic melanoma with features of blue nevus and tumoral melanosis identified during pembrolizumab therapy - Matthew F. Helm, MD; Michael J. Bax, MD; Paul N. Bogner, MD; Catherine G. Chung, MD (Elsevier, 2017)
Metastatic melanoma may exhibit clinical or histologic features of blue nevus. Pembrolizumab therapy is associated with regression and tumoral melanosis. We report on a man with widespread metastatic melanoma on pembrolizumab therapy in whom a blue-grey papule developed on the left side of his neck that clinically resembled a blue nevus and histologically showed features of both blue nevus and tumoral melanosis. The subtle melanocytic component and prominent changes of regression evident on biopsy suggest that his immunomodulatory therapy may have influenced the histologic findings noted on biopsy. Physicians that treat patients with metastatic melanoma should be aware of the spectrum of histologic findings evident on biopsy not only to allow for early diagnosis but to also better understand the effects of treatment.